RELAÇÃO ENTRE OS FATORES DE RISCO PARA LESÃO EM ATLETAS DE FUTSAL MASCULINO (Movimenta (ISSN 1984-4298), 2021)
The aim of this study was analyze risk factors for injury in male futsal players. This transversal study included fifteen male futsal players (21.80±3.21 years), and performed the functional tests: a) evaluation of the function of the hip extensor muscles (Single leg bridge test); b) evaluation of the lumbopelvic/CORE function (Prone bridge test); c) evaluation of the functional performance of the lower limbs (single hop test, timed hop test and side hop test); d) assessment of range of motion (ROM) of ankle dorsiflexion (Lunge test).  Most of the players had high risk in muscle function of the hip extensors, on both sides (53.3%), deficit in the lumbopelvic/CORE function (66.7%), and functional performance of both lower limbs (57.14%).  Players presented important risk factors for injuries, and preventive actions in this context is suggested.
Keywords: Athletic Injuries. Risk Factors. Athletes.